Talenta Prestatif: Membangun Bakat dan Minat Berprestasi - Riska Amalia; Masduki Asbari; Novia Anisawati (AGUSPATI RESEARCH INSTITUTA, 2023)
The aim of this study is to identify talents who excel through the courage to take risks and decisions. This study uses a descriptive qualitative method by taking note-taking because the data source was obtained by listening to the oral narrative from the Indonesian Ministry of Education and Culture's YouTube channel entitled